Legal Regulations for Shrimp Ponds in Coastal Areas in NTB - Permata, Nathania; Alvina, Hera (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Indonesia's coastal areas hold strategic value as productive areas that support economic activity, one of which is through shrimp farming. West Nusa Tenggara (NTB) is one of the main centers of national shrimp production, contributing significantly to foreign exchange and employment. However, the rapid expansion of shrimp farming has given rise to environmental, social, and legal issues, primarily due to the lack of specific regulations at the regional level governing sustainable shrimp farming management. This lack of regulation has resulted in weak oversight, a high potential for coastal water pollution, mangrove ecosystem degradation, and conflicts over land use. This study aims to analyze the legal regulations regarding shrimp farming in the coastal areas of NTB province and to identify emerging legal challenges. This study uses normative legal methods with a statutory and conceptual approach. The research findings show that while national legal frameworks such as the Fisheries Law, the Coastal Area and Small Islands Management Law (PWPPK), and their derivative regulations provide a general basis for spatial planning and licensing, their implementation at the regional level still faces regulatory gaps, as evidenced by low compliance with shrimp pond permits in West Nusa Tenggara (NTB). This highlights the urgency of establishing a specific Regional Regulation (Perda) in NTB to ensure alignment between economic development and coastal ecosystem protection. Clear regulations are expected to ensure the sustainability of shrimp farming businesses while maintaining a balance between economic interests, the environment, and the well-being of coastal communities.